Structure elucidation of cyclohexene (9Z)-octadec-9-enyl ethers isolated from the leaves of Uvaria cherrevensis (Annonaceae) - Chiramet Auranwiwat (2019)
© 2019 The phytochemical investigation of the leaf extract of Uvaria cherrevensis (Annonaceae) yielded three new cyclohexene (9Z)-octadec-9-enyl ethers, cherrevenols M-O (1–3), and a known fatty ester derivative (4). The structures of the isolated compounds were elucidated by spectroscopic and computer-aided molecular modelling methods. Ozone Induced Dissociation (OzID) mass spectrometry was employed to determine the C-9 position of the side chain olefinic double bonds, while 13 C NMR spectroscopy indicated their (Z)-configurations. All isolated compounds were evaluated for their antimalarial and cytotoxic activities; all were inactive.